I rapporti Ue/America Latina fra desideri e realtà - Campanella, Raffaele (Rivista di studi politici internazionali, 2010)
The Sixth EU-Latin America and Caribbean Summit (Madrid, 18 May 2010) acknowledged the incomplete realization of the ambitious project launched in 1999 in Rio (Brazil) whose goal was to create a ‘Bi-regional Strategic Partnership’. In fact, despite long bilateral and multilateral negotiations, the Eu/Mercosur Association Agreement has not been signed yet. Such an agreement, aiming at creating a broad market of near 750 million people, would have been a significant improvement in the relations between the two regions. Meanwhile, specific agreements are being reached (Eu/Central America, Eu/Peru, Eu/Colombia), adding up to the already existing ones (Eu/Mexico, Eu/Chile). New sectors of cooperation are appearing (investments, infrastructures, energy, Smes, cultural heritage, environment, climate change, fight on terrorism, drugs and trans-national organized crime): knowledge as a whole becomes relevant (science, research, innovation and technology). A Eu-Latin America Foundation will be created. In the meantime, a new Oas excluding the US and Canada is emerging through the creation of a Community of Latin American and Caribbean States (Calc), adding itself to the existing Unasur and Alba. A new model of regional integration is emerging in L.A. different from the European one. Le sixième sommet Union Européenne/Amérique Latine et Caraïbes, réuni à Madrid le 18 mai 2010, a pris acte de la réalisation seulement partielle de l’ambitieux projet lancé à Rio en 1999 visant à faire naître un ‘partenariat stratégique birégional’. En effet, malgré de longues négociations bilatérales et multilatérales (dans le cadre du Doha Round notamment), la conclusion de l’accord d’association Ue/Mercosur n’a toujours pas vu le jour. Un tel accord, visant à créer un vaste marché de près de 750 millions de personnes, aurait constitué un véritable saut qualitatif dans les rapports entre les deux régions. Se dessinent en revanche des accords spécifiques (Ue/Amérique centrale, Ue/Pérou, Ue/Colombie), qui s’ajoutent à ceux déjà existants (Ue/Mexique, Ue/Chili). En même temps se multiplient les secteurs de coopération (investissements, infrastructures, énergie, PME, patrimoine culturel, environnement, changement climatique, lutte contre la drogue et la criminalité organisée): une attention particulière est consacrée à l’économie de la connaissance (science, recherche, innovation, technologique). Une Fondation Ue/Amérique Latine devrait également voir le jour. Entre temps se profile en Amérique latine une nouvelle Oea excluant États-Unis et Canada, à travers la création d’une Communauté des États d’Amérique Latine et des Caraïbes (Calc), qui s’ajouterait à l’Unasur et à l’Alba. Une nouvelle forme d’integration différente du modèle européen se dessine en A.L.. PAROLE CHIAVE: Associazione strategica biregionale; Sesto vertice Ue-Alc; Investimenti europei in America Latina; Spazio Ue-Alc della conoscenza; Nuove forme di integrazione.